Manajemen Kurikulum Muatan Lokal Berbasis Religius Sebagai Upaya Membentuk Karakter Islami Siswa - Iin, Nurhayati (Prosiding University Research Colloquium, 2021)
Management is a process of planning, implementation and evaluation compiled by a group or individual in order to achieve a common goal. Religious-based local content curriculum is curricular and extracurricular activities to develop competencies that are tailored to the characteristics and potential of the region, including regional advantages, whose material cannot be grouped into existing subjects. This type of research is qualitative, namely research that intends to understand the phenomenon of what is experienced by the research subject such as behavior, perception, motivation, action, presented by way of description in the form of words and language, in a special context that is natural and by utilizing various scientific methods. Data collection techniques in this study are by conducting observations, interviews and field notes.The steps in analyzing the data are data reduction, data presentation, and drawing conclusions. The results of this study indicate that the religious-based local content curriculum has an effect on the character and development of students.